Antidiabetic activity of Averrhoa bilimbi fruit methanol extract through enhancement of GLUT4 protein expression in diabetes‐induced mice - Greselita Yolanda Juniyanti; Hesti Oktapiani; Ahmad Ridwan (Indonesian Journal of Biotechnology, 2024)
GLUT4, the glucose transporter responsive to insulin, is primarily found in muscle and adipose tissues. Diabetes can result from impaired insulin secretion and sensitivity. This study aims to evaluate the antidiabetic properties of Averrhoa bilimbi methanol extract by enhancing GLUT4 protein expression in mice with induced diabetes. Extraction was conducted via soxhletation using 96% methanol. Phytochemical analysis, employing qualitative tests and GC‐MS, was performed. Antioxidant activity (IC50) and toxicity (LD50) were analyzed using DPPH and OECD methods. This research followed an experimental post‐only control group design, with mice intraperitoneally injected with 150 mg/kg BW of alloxan monohydrate. A total of 24 mice were then divided into six groups: Normal, Negative Control, Positive Control (metformin), Low Dose (50 mg/kg BW), Medium Dose (250 mg/kg BW), and High Dose (300 mg/kg BW). Treatment lasted 21 days, with fasting blood glucose and body weight measurements taken every three days. On day 21, the liver and skeletal muscle were isolated, and blood was collected. Serum insulin and GLUT4 expression were assessed via ELISA and Western Blot, respectively. Phytochemical screening revealed flavonoids, saponins, terpenoids, tannins, and phenols and their derivatives. The IC50 value was 85 µg/mL, with an LD50 value of 1,000 mg/kg BW, indicating strong antioxidant activity and mild toxicity. The extract significantly reduced blood glucose levels but did not impact weight loss in diabetic mice. Average liver weight and index were highest in the Negative Control group, yet the lowest levels of hepatic and muscle glycogen were also observed in this group. Interestingly, insulin level and HOMA‐IR decreased in diabetic mice, while the Medium Dose group exhibited the highest GLUT4 expression levels. In conclusion, medium doses of A. bilimbi methanol extract hold potential for diabetes treatment, with a probable mechanism of targeting GLUT4 protein expression.